The Effect of Hydrochloric Acid Solution and Glycerol on The Mechanical, Hydrate Properties and Degradation Rate of Biofilm from Ripe Banana Peels - Putri Ramadhany; Justin Kenny Hardono; Maria Gabriela Kristanti (Jurnal Rekayasa Proses, 2021)
Banana peel is a biomass waste that has not been utilised optimally, despite its high starch content. Moreover, starch has potential as a raw material for biofilm or edible film production. This research focused on using the starch content from the mature banana peel to create a biofilm. Starch was extracted from the banana peel; then, it was hydrolyzed with a variation of hydrochloric acid solution (HCl) of 0.5 M (0, 2, 4 %-v/v Starch). Glycerol (0, 20, 40 %-w/w starch) was used as a plasticizer. It was found that the formulation of 4%-v/v HCl solution and glycerol 20%-w/w resulted in the highest biofilm’s tensile strength of 4.18 MPa. However, the elongation break percentage achieved the best result at 20,2% when the formulation of 0%-v/v HCl solution and 40%-w/w glycerol was applied. Increasing HCl solution and glycerol was proven to improve the biofilm’s solubility in the water, where 47.9% solubility was attained in the formulation of 40%-w/w glycerol and 4%-v/v HCl solution. The degradation rate of biofilm in the soil was measured using zero- and first-order kinetic rates. The zero-order resulted in the best model with a half-life time (t1/2) between 73 to 108 days.